2014
DOI: 10.1139/cjfas-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Breeding site selection by coho salmon (Oncorhynchus kisutch) in relation to large wood additions and factors that influence reproductive success

Abstract: The fitness of female Pacific salmon (Oncorhynchus spp.) with respect to breeding behavior can be partitioned into at least four fitness components: survival to reproduction, competition for breeding sites, success of egg incubation, and suitability of the local environment near breeding sites for early rearing of juveniles. We evaluated the relative influences of habitat features linked to these fitness components with respect to selection of breeding sites by coho salmon (Oncorhynchus kisutch). We also evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
2
6
0
Order By: Relevance
“…Delays in spawning have been documented in many salmon species due to warm water temperatures (Webb and McLay 1996;Richter and Kolmes 2005;Quinn 2018). These results are also consistent with prior anecdotal observations (Neave 1943;Sandercock 1991;Clark 2013), which reported that initial annual peak discharge events tend to occur before the initiation of redd building for Coho Salmon.…”
Section: Are Patterns Of Movement In Migration or Spawning Initiationsupporting
confidence: 92%
“…Delays in spawning have been documented in many salmon species due to warm water temperatures (Webb and McLay 1996;Richter and Kolmes 2005;Quinn 2018). These results are also consistent with prior anecdotal observations (Neave 1943;Sandercock 1991;Clark 2013), which reported that initial annual peak discharge events tend to occur before the initiation of redd building for Coho Salmon.…”
Section: Are Patterns Of Movement In Migration or Spawning Initiationsupporting
confidence: 92%
“…We observed an increased frequency of multiple channels and pools with wood cover near the confluences of large tributaries, and in some cases (e.g., downstream reaches), we attributed the increased sediment and wood supply to the creation of patches of spawning habitat. Proximity of spawning habitat to complex cover is important for spawning site selection, but previous studies have focused on the proximity of redds to cover rather than the potential importance of cover as a driver of redd density (Senter and Pasternack 2011;Clark et al 2014). This is consistent with our observation of greater spawning within complex reaches, where adult holding pools and cover occurred in close proximity, but our modeling approach directly linked cover to increased redd densities in 3-km reaches.…”
Section: Variation In Spawning-habitat Relationships Across Spatial Ssupporting
confidence: 85%
“…Recent research suggests that spawning sites are associated with complex habitat types that support offspring after emergence (Falke et al 2013). For example, Clark at al. (2014) found that the proximity to complex juvenile rearing habitat, which likely increases reproductive success by conferring a survival advantage to juveniles, was important for spawning site selection.…”
Section: Implications Of Riverscape Spawning Patterns For Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Wood was arranged into 37 log jams. Large wood, as considered herein, consisted of pieces ≥ 15 cm in diameter and 3 m in length (Clark et al 2014;Jones et al 2014).…”
Section: Methodsmentioning
confidence: 99%